Methodology For The Analysis Of Oxygen Saturation And Heart Rate In The Development Of Online Classes, In Children, Product Of The COVID-19 Pandemic - et. al., Wilver Auccahuasi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In these times of pandemic caused by COVID-19, many of the activities we carry out are changing, education is one of the main ones that changed considerably and in the face of this change, certain manifestations that normally could not be identified are taking place, such as This is the case of the pressure and stress that the students are being subjected to, due to the fact that they spend most of the day at home in a kind of voluntary confinement, added to the realization of online classes from home, With parents attentive to the class, being able to understand teachers, conducting evaluations, among others, present in students an increase in pressure and levels of stress that are commonly subjected. The methodology that is proposed is related to being able to evaluate the level of oxygen saturation and the heart rate that they are developing in the realization of the online classes, this evaluation is carried out using low-cost devices known as clocks. intelligent, the results show that depending on the age the students are able to distinguish the different pressures that are manifested in the variability of the heart rate, we can indicate that at an older age the students can distinguish these pressures, it is concluded that it is possible to perform these measurements with The following purposes, the first to be able to monitor the students if they present any symptoms of COVID-19 and second if they present any manifestation of a possible problem related to the respiratory and cardiac system, the study recommends keeping in mind the manifestations that the students are developing. students in online classes and it is very helpful to be able to assess these vital signs to to be able to assess these manifestations as a result of pressure and stress.